Internally Commissioned External Review (ICER) at the International Food Policy Research Institute (IFPRI) - Joubert, Marina (International Food Policy Research Institute, 2003)
Within IFPRI there is widespread recognition of the fact that research is not an end in itself, but can only have meaning and impact once the results are effectively communicated. The Communication Division faces the challenge of communicating about IFPRI (corporate communication) and communicating its research results (science and policy communication) in an integrated manner. Even more, IFPRI also have to contribute to awareness of agricultural development within the global policy arena.